Effect of Nd and Nb co-doping on the structural, magnetic and optical properties of multiferroic BiFeO3 nanoparticles prepared by sol-gel method. Issue 5 (1st April 2017) - Wang, Ting; Xu, Ting; Gao, Shang; Song, S.-H.
Abstract: BiFeO3, BiFe0.95 Nb0.05 O3 and Bi1− x Nd x Fe0.95 Nb0.05 O3 ( x =0.0, 0.05, 0.10, 0.15 and 0.20) nanoparticles are successfully synthesized via a tartaric acid-assisted sol-gel technique for the first time. The effect of Nd and Nb co-doping on the structure, morphology, and magnetic and optical properties is investigated. X-ray diffraction (XRD) and Raman measurements demonstrate that Nd 3+ ions and Nb 5+ ions co-doping at A and B-sites of BiFeO3 can result in a structural transformation (from single rhombohedral phase ( R 3 c ) to two coexisting phases ( R 3 c and Pbam)). The morphology of the nanoparticles seems to be approximately cubic, and by the co-doping, the size of the nanoparticles decreases from ~132 to ~35 nm. Notable improvement in the remanent magnetization of the sample with x =0.15 is observed with a value of 0.285 emu/g, being 20 times higher than that of the undoped sample (BiFeO3 ). A decrease in the optical band gap is also observed in the Nd and Nb co-doped nanoparticles, indicating their favorable potential in photocatalytic applications.